Standardized Kaempferia parviflora Extract Inhibits Intrinsic Aging Process in Human Dermal Fibroblasts and Hairless Mice by Inhibiting Cellular Senescence and Mitochondrial Dysfunction. (2nd August 2017) - Park, Ji-Eun; Woo, Seon Wook; Kim, Mi-Bo; Kim, Changhee; Hwang, Jae-Kwan
Abstract : Intrinsic skin aging is a complex biological phenomenon mainly caused by cellular senescence and mitochondrial dysfunction. This study evaluated the inhibitory effect of Kaempferia parviflora Wall ex. Baker ethanol extract (KPE) on H2 O2 -stimulated cellular senescence and mitochondrial dysfunction both in vitro and in vivo. KPE significantly increased cell growth and suppressed senescence-associated β -galactosidase activation. KPE inhibited the expression of cell-cycle inhibitors (p53, p21, p16, and pRb) and stimulated the expression of cell-cycle activators (E2F1 and E2F2). H2 O2 -induced hyperactivation of the phosphatidylinositol 3-kinase/protein kinase B (AKT) signaling pathway was suppressed by KPE through regulated expression of forkhead box O3a (FoxO3a) and mammalian target of rapamycin (mTOR). KPE attenuated inflammatory mediators (interleukin-6 (IL-6), IL-8, nuclear factor kappa B (NF- κ B), and cyclooxygenase-2 (COX-2)) and increased the mRNA expression of PGC-1 α, ERR α, NRF1, and Tfam, which modulate mitochondrial biogenesis and function. Consequently, reduced ATP levels and increased ROS level were also reversed by KPE treatment. In hairless mice, KPE inhibited wrinkle formation, skin atrophy, and loss of elasticity by increasing the collagen and elastic fibers. The results indicate that KPE prevents intrinsic aging process in hairless mice by inhibiting cellular senescence and mitochondrial dysfunction, suggesting its potential as a natural antiaging agent.